Analisis Makna konotatif dan Budaya Jepang: “Iblis” dalam Kanji Ber-Bushu Oni - Ngaziz, Malik; Mulyadi, Budi (Vocational College of Diponegoro University, 2025)
This study examines four kanji characters containing the bushu oni (鬼) that do not lexically mean